2007
DOI: 10.1097/01.aog.0000287615.35425.5c
|View full text |Cite
|
Sign up to set email alerts
|

Management of Shoulder Dystocia

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(26 citation statements)
references
References 28 publications
3
21
2
Order By: Relevance
“…This finding implies that inadequate screening for glucose intolerance and superficial treatment of diabetes are conducive to these injuries. This being the case, implementation of the proposed measures could probably reduce the rate of shoulder dystocia markedly both in America and in other countries, where its rate has also increased in recent years [1,9,[33][34][35][36]. The "CESDI Committee", having investigated shoulder dystocia related fetal deaths in England, Wales and Northern Ireland, found substandard intrapartum management the most frequent causative factor [3].…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that inadequate screening for glucose intolerance and superficial treatment of diabetes are conducive to these injuries. This being the case, implementation of the proposed measures could probably reduce the rate of shoulder dystocia markedly both in America and in other countries, where its rate has also increased in recent years [1,9,[33][34][35][36]. The "CESDI Committee", having investigated shoulder dystocia related fetal deaths in England, Wales and Northern Ireland, found substandard intrapartum management the most frequent causative factor [3].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the injury is independent of the experience of the clinician (Jennett et al 1992;Mollberg et al 2005b;Wolf et al 2000) (Table II) 5. The frequency of Erb's palsy is increasing slightly or remaining the same (Gurewitsch et al 2006;Graham et al 1997;Gordon et al 1973;Bager 1997;MacKenzie et al 2007;Mollberg et al 2005a;Boyd et al 1983;Evans-Jones et al 2003), despite the universal call for gentleness in the literature of the 1980s and early 1990s (Table III) 6. Fracture of the clavicle has been described by Chez (Chez et al 1994) as 'an unpredictable, unavoidable complication of normal labour' (due to maternal labour forces).…”
Section: Erb's Palsy (Bpi): What Is the Cause?mentioning
confidence: 96%
“…Bager (1997) reported an increase of BPI in Sweden from 1980 (1.3/1000) to 1994 (2.2/1000). MacKenzie et al (2007) at the University of Oxford reported that 'by 2001, regular training sessions for labour ward staff on the management of shoulder dystocia were being conducted in our obstetric unit, as in many other units. By 2004, the routine monthly performance indicators of problem deliveries in the unit indicated that there seemed to be an increasing number of cases of shoulder dystocia and possibly also brachial plexus injuries and this prompted the present study'.…”
Section: Is Shoulder Dystocia Under-reported?mentioning
confidence: 99%
See 1 more Smart Citation
“…Common elements between the various algorithms are to perform McRoberts’ manoeuvre and suprapubic pressure in the first instance, and a failure of these two methods should be followed by other manoeuvres such as rotational methods, posterior arm delivery and all- fours manoeuvre. More injurious manoeuvres such as clavicular fracture, symphysiotomy and Zavanelli manoeuvres are rarely used due to the high success rates of the less invasive manoeuvres [5, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%